Complementary Ureterorenoscopy after extracorporeal Shock Wave Lithotripsy in proximal ureteral stones: success and complications - Demirelli,Erhan (2022)
SUMMARY OBJECTIVE: The aim of this study was to demonstrate the effect of extracorporeal shock wave lithotripsy application on the success and complications of ureteroscopic lithotripsy in proximal ureter stones. METHODS: The data of 87 patients who did not respond to shock wave lithotripsy and underwent ureteroscopic lithotripsy were retrospectively analyzed and classified as group I, and 99 patients who received ureteroscopic lithotripsy as primary treatment were classified as group II. Demographic features, response to treatment, and preoperative and postoperative complications were compared between the two groups. RESULTS: There was no difference between the two groups in terms of gender, operation times, stone sizes, and ureteroscope diameters. (p>0.05). Infective complications such as postoperative fever, pyelonephritis, and urosepsis were similar in both groups (p=0.142, p=0.291, and p=0.948). Stone migration was observed in 10 (11.5%) and 6 (6.1%) patients in groups I and II, respectively (p=0.291). Impacted stone was seen in 47 (54%) patients in group I and in 15 (15.2%) patients in group II (p<0.0001). Mucosal laceration occurred in 11 (12.6%) and 3 (3%) patients in groups I and II, respectively (p=0.028). Ureteral perforation was detected in 3 (3.4%) patients in group I and 1 (1%) patient in group II, whereas ureteral avulsion was not observed in either group (p=0.524). CONCLUSIONS: It was concluded that the application of shock wave lithotripsy before ureteroscopic lithotripsy in proximal ureter stones did not affect the success. Although the results are similar in terms of postoperative infection, shock wave lithotripsy application has been found to increase the risk of stone impaction into the mucosa and ureteral laceration.